KONTRIBUSI KELINCAHAN DAN KECEPATAN DENGAN KEMAMPUAN DRIBBLING ATLET SEPAKBOLA SSB BANTAR MUDA - Ali, Ridwan; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT. The problem in this research is still low ability athletes dribbling soccer SSB Bantar Muda, who allegedly due to lack of agility and speed. Thus, this study aims to describe the contribution of agility and speed either individually or jointly. With the dribbling ability of football athletes Muda Stars SSB 2015. The study population was a football athlete SSB Bantar Muda in 2015, amounting to 75 people. Sampling was done by using sampling porpusive ie age group 17 to 20 years of age who berjulamlah 30 people, the instrument is used; (1) test zig-zag run, to measure the agility variable, (2) a test run of 50 yards (45 meters) to measure the variable speed, (3) test capability to measure a variable dribbling dribbling skills. Data were analyzed using product moment correlation and multiple correlation with the formula determined. The aim of research shows; (1) there is a significant relationship between agility with dribbling skills, agility, contributing 43.30% to the dribbling skills, (2) there is a significant correlation between the speed with dribbling skills. 24.21% contribution rate, (3) there is a significant relationship between agility and speed together with dribbling skills, agility and speed contributed to the ability of dribbling 43.59%.Keywords : Agility, Speed, Dribbling